(untitled) (The Research of Medical Science Review, 2025)
The synthesis of innovative organic compounds has gained significant attention due to their diverse biological activities. Hydrazides have emerged as promising candidates due to their pharmacological relevance, biological potential, and commercial applicability. Previously, various hydrazide derivatives have been synthesized using simple hydrazines. To our knowledge, none of the earlier research used phenyl hydrazines to synthesize hydrazide analogs. Leveraging this knowledge gap, novel phenolphthalein hydrazides were synthesized via reactions of substituted phenyl hydrazine derivatives in an ethanol solvent. The successful formation of all analogs was monitored by thin-layer chromatography and confirmed through UV, IR, and NMR spectroscopic analyses. The synthesized derivatives exhibited antibacterial properties, especially against Staphylococcus aureus (Gram-positive) bacteria. The application test was designed as a prototype investigation to provide preliminary results, underscoring the great potential of these phenolphthalein hydrazides as anticancer, anti-inflammatory, antioxidant, and antidiabetic agents, bioimaging probes, pH-sensitive drug carriers, enzyme inhibitors, and metal chelators for therapeutic applications.